EKSISTENSI TIM INTERVENSI BERBASIS MASYARAKAT DALAM MEMBERANTAS PENYALAHGUNAAN NARKOTIKA DI DESA SANGSIT - Kadek Arya Putra Gunawan; I Nyoman Bagiastra (Jurnal Komunikasi Hukum, 2024)
This research aims to find out how the existence of this community-based intervention team is in dealing with narcotics abuse, both the efforts and the obstacles experienced in eradicating narcotics abuse. This research applies empirical legal research methods with data collection techniques, namely observation, interviews and documentation. There are data processing techniques that apply qualitative descriptive analysis through the process of data collection, data reduction, data presentation and drawing conclusions. The results of this research conclude that the efforts carried out include pre-emptive and preventive as well as the obstacles experienced. The obstacles experienced when it was first formed were underestimated by the community and were constrained by service locations and funds, access to IBM was very limited to assistance and supervision and family or parents. Relatively many people refuse to have their children rehabilitated.